2015
DOI: 10.1017/s2040174415001208
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of maternal undernutrition on offspring carotid artery remodeling: role of miR-29c

Abstract: The purpose of this study was to examine the hypothesis that excess maternal glucocorticoids in response to maternal undernutrition programs the expression of extracellular matrix (ECM) components potentially by miR-29c. We measured the expression of mRNA (qRT-PCR) and protein (Western blot) for collagen 3A1, collagen 4A5 and matrix metalloproteinase 2 (MMP2) in offspring carotid arteries from three groups of dams: 50% food-restricted in latter half of gestation [maternal undernutrition (MUN)], MUN dams who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Clinical and experimental data have revealed deleterious adaptations in the vasculature as a hallmark of the fetal programming process. [1][2][3][4][5][6][7][8][9][10][11] These responses are attributed to insults (e.g. maternal diet manipulation, hypoxia, and uteroplacental insufficiency) that occur during the critical window of fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and experimental data have revealed deleterious adaptations in the vasculature as a hallmark of the fetal programming process. [1][2][3][4][5][6][7][8][9][10][11] These responses are attributed to insults (e.g. maternal diet manipulation, hypoxia, and uteroplacental insufficiency) that occur during the critical window of fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, miR-29c could inhibit endotheliocyte migration and angiogenesis of human endothelial cells by suppressing the insulin like growth factor 1 [30]. Khorram O et al also found that miR-29 played vital roles in atherosclerosis by regulating the expression of extracellular matrix [31]. These preclinical studies indicated that miR-29c could play several distinct roles during atherosclerosis development; thus, they provide underlying molecular mechanisms for our results.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 60%
“…Finally, we studied only miR-29c in our research. But many previous basic studies from references indicated that miR-29c may play an important role in the development of atherosclerosis through many mechanisms [14,30,31]. Therefore, those basic researches mentioned in the previous literatures provided a certain theoretical guarantee for our conclusion.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 63%
“…The hypertension may be associated with salt sensitivity [67]. Undernutrition in sheep dams leads to increased expression of several extracellular matrix proteins in the carotid arteries, related in part to suppression of miR-29c that may involve glucocorticoids [68•]. Low-protein diet during pregnancy has been reported to lead to enhanced responsiveness to angiotensin II [69], especially in male off-spring [70], and exaggerated proliferative response to vascular injury in the offspring with increased expression of genes related to oxidative stress [71].…”
Section: Pathogenesis Of Primary Pediatric Hypertensionmentioning
confidence: 99%